Epidemiological Situation on Tick-Borne Viral Encephalitis in the Russian Federation in 2019 and Forecast for 2020 - A. Ya. Nikitin; E. I. Andaev; E. V. Yatsmenko; Yu. N. Trushina; M. I. Tolmacheva; E. V. Verigina; A. O. Turanov; S. V. Balakhonov (Проблемы особо опасных инфекций, 2020)
Tick-borne encephalitis is a transmissible natural-focal disease which occurs in some countries across Europe and Asia. The observation of epidemic process dynamics of TBVE in Russia covers an 80-year long period and it’s the world longest. The existence of extensive records, various data from different geographic and administrative areas opens the way to interpretation of certain ecological and social factors and their role in the regional epidemiological situation. The targeted measures against TBVE are feasible only when the role of basic predictors of decreasing incidence is defined. Objective: analysis of TBVE incidence among the population and preventive measures in the Districts and constituent entities of Russia in 2019, forecast for 2020 based on the data collected in 2010–2019. The article shows a continued downward trend in TBVE incidence, noted in recent years. However, cases of infection were registered in 6 Federal Districts and 46 regions just like in the past. The number of patients amounted to 1559 (the incidence rate is 1.02 per 100000 people), of whom 23 have died. The rate of seeking medical care among those who were bitten by ticks increased. Specific preventive measures against TBVE haven’t significantly changed by volume and focus compared to the previous period. The scope of acaricide treatments has declined. The article also presents the data concerning TBVE carriers’ infection rate, and the laboratory study results in districts and regions across the country. It is recognized that the epidemiological situation on TBVE in Russia is still unfavorable. It requires the constant attention of health facilities and Rospotrebnadzor and management decisions aimed at further decrease in the incidence by improved prevention especially in the regions with high TBVE incidence.